ETHNIC AND DEMOGRAPHIC CHANGES IN SKOPJE IN THE FIFTIES OF THE XX CENTURY (Annual of the Faculty of Philosophy in Skopje, 2011)
In the fifties of the last century significant demographic and ethnic changes occurred in Skopje and the Skopje area. The population grew rapidly in the period of 1948 till 1961, the population only in the city increased by almost 80,000 residents.Another important factor that affected the ethno demographic structure of the city and its area is the fact that part of Turks and other Muslim population emigrated and numerous immigrants from the Kosovo and Metohija area and Sandžak, as well as from other areas in Macedonia settled down in the city.The city rapidly changed its physiognomy as a consequence of the rapid increase of its inhabitants. These settlers were mostly concentrated in the corebf the old city or in the peripheral neighborhoods, living under low standard housing conditions, often in illegally built settlements. Large number of negative consequences occurred such as economy problems, health problems, and a growing percentage of unemployment, because of the mass migration. In the analysis of the leadership in Macedonia already in the mid fifties was concluded that the mass migration in Macedonia and especially in Skopje was a serious problem.
Keywords: ETHNIC - DEMOGRAPHIC CHANGES; MIGRATIONS; ETHNIC MOVEMENTS; SKOPJE; SKOPJE AREA; CENSUS OF POPULATION